Educated expectations: graduate mothers and their work in the long 1950s - Golding, LA (2022)
This thesis opens up original perspectives on middle-class women’s lives in post-war Britain by bringing together and interrelating their experiences of different types of work. By developing an analysis informed by the history of emotions, the scholarship of feminist economics and the ethics of care, it illuminates the ways in which work – paid or unpaid, caring, domestic or voluntary – impacts self-fulfilment and contributes to the sense of self. It addresses together different aspects of educated women’s lives, which have tended to be addressed separately in historical scholarship. It is based on the data set contained in the papers of the social scientist Dr Viola Klein. Using over nine hundred completed questionnaires from a 1963 social survey and accompanying notes and letters, contextualised by published social surveys, statistics, correspondence and oral history, it examines how graduate women conceptualised the ways in which they combined domestic responsibilities with an intellectual life. The nuancing of middle-class women’s approach to work is made possible through the finely textured detail of responses to Klein’s survey. Many women were motivated to work by a desire for intellectual fulfilment and a role beyond that of wife and mother. This thesis demonstrates that many middle-class mothers could gain a sense of agency by arranging their lives so that they were able to achieve intellectual fulfilment alongside family life. Although there were undoubtedly compromises and frustrations, the process of reflection and negotiation could be creative. Teaching was a popular form of work for women graduates in post-war Britain, and there were increasing opportunities for those who had studied medicine or dentistry at university to practice within the new National Health Service. The widening of these professional fields raised fundamental questions about the interrelationships between paid and unpaid caring, domestic and voluntary work, motherhood and marriage.